ENVIRONMENT IMPACT AND CARBON FOOTPRINT ASSESSMENT OF OIL PRODUCTION FROM PLASTIC WASTE: A CASE STUDY OF SMALL-SCALE FACTORY - Kongroy, Porntawee; Pinawet, Thanawan (Life Sciences and Environment Journal, 2022)
This research presents the results of the environmental impact assessment and carbon footprint of oil production from plastic waste in Thailand, utilizing the ISO 14040 series guidelines and Life Cycle Assessment (LCA) ReCiPe 2016 Midpoint method. The assessment takes into account the activities of raw material acquisition, transportation and production processes in the factory (Candle to Gate), including the amount of waste and air emissions. The study showed 18 indicators of midpoint impact. Combustion of fuel to generate heat energy in the production process is considered a significant factor in the impact on environment. It was found that 1 cycle of oil production (3,000 kg) has a global warming of 13,200 kg carbon dioxide equivalent (kgCO2-eq), fine particulate matter formation of 13.4 kg equivalent (kgPM2.5-eq) and water consumption 29.7 m3, associated with the endpoint impact on 3 indicators: human health impact (0.177 daily), ecosystem damage impact (0.000332 species.year) and resource depletion impact (0.593 USD2013). For the Carbon Footprint assessment, there was an overall total value of 528 tonnes of carbon dioxide equivalent per year (tonCO2-eq /year) based on oil production at 40 cycles/year. The results of this research can be used as a basis for improving the production process and considering an alternative fuel. It is also used as a policy guide for decision-making on environmentally-friendly activities. This will contribute to the sustainable development of energy and the environment of Thailand.